Covalent C–N Bond Formation through a Surface Catalyzed Thermal Cyclodehydrogenation - Piskun, Ilya; Blackwell, Raymond; Jornet-Somoza, Joaquim; Zhao, Fangzhou; Rubio, Angel; Louie, Steven G; Fischer, Felix R (Journal of the American Chemical Society, 2020)
The integration of substitutional dopants at predetermined positions along the hexagonal lattice of graphene-derived polycyclic aromatic hydrocarbons is a critical tool in the design of functional electronic materials. Here, we report the unusually mild thermally induced oxidative cyclodehydrogenation of dianthryl pyrazino[2,3-g]quinoxalines to form the four covalent C–N bonds in tetraazateranthene on Au(111) and Ag(111) surfaces. Bond-resolved scanning probe microscopy, differential conductance spectroscopy, along with first-principles calculations unambiguously confirm the structural assignment. Detailed mechanistic analysis based on ab initio density functional theory calculations reveals a stepwise mechanism featuring a rate determining barrier of only ΔE ⧧ = 0.6 eV, consistent with the experimentally observed reaction conditions.